2019
DOI: 10.3390/nu11010093
|View full text |Cite
|
Sign up to set email alerts
|

Dual Anticoagulant/Antiplatelet Activity of Polyphenolic Grape Seeds Extract

Abstract: Because of the side-effects of commonly used anti-platelet and anticoagulant drugs, investigations into plant substances with similar activities are very common. Based on our own studies in recent years, we estimate that it is possible to use natural compounds to both inhibit coagulation pathway enzymes and to reduce blood platelets’ activation. As such, in our current study we wanted to verify the anti-platelet and anticoagulant properties of grape seed extract (GSE) using in vitro models. During our analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 44 publications
(49 reference statements)
1
26
0
3
Order By: Relevance
“…For this reason, in the last decade an ever-increasing interest in the seeds appeared, since they contain bioactive compounds such as fatty acids and polyphenols [5,[10][11][12][13][14], which are attractive from a nutraceutical perspective [15][16][17][18][19][20][21][22]. Their potential benefits ranges from anti-platelet and anticoagulant activity, to antioxidant, hypoglycemic, and even activity against cancer [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in the last decade an ever-increasing interest in the seeds appeared, since they contain bioactive compounds such as fatty acids and polyphenols [5,[10][11][12][13][14], which are attractive from a nutraceutical perspective [15][16][17][18][19][20][21][22]. Their potential benefits ranges from anti-platelet and anticoagulant activity, to antioxidant, hypoglycemic, and even activity against cancer [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, some studies have demonstrated no significant antiplatelet effect in hypertensive populations [93,94,96] (Table 1). Chokeberries and grapes used in these intervention studies are food sources that have previously shown antiplatelet effects in vitro [43,113]. This may highlight that biological variables and different baseline platelet functions of study populations may lead to differences in the antiplatelet effect of polyphenols.…”
Section: Evaluation Of Methods Used For Polyphenol Antiplatelet Studiesmentioning
confidence: 99%
“…The enzyme-linked immunoassay (ELISA) method can also be used to count and perform functional analysis on PMPs but without size information [39]. In addition, the vasodilator-stimulated phosphoprotein (VASP) phosphorylation assay is a special flow cytometry method that has been used in research studies to evaluate platelet function [42][43][44]. It works on the principle that activation of the P2Y 12 receptor by ADP reduces VASP phosphorylation and thus inhibition of receptor activation increases VASP phosphorylation.…”
Section: Other Platelet Function Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of using different agonists of aggregation is assessment of different signaling pathways that are inhibited. Quite often concentrations of extract are arbitrarily used in the studies, e.g., grape (Vitis vinifera L.) seed extracts reduced platelet aggregation in the test induced by ADP in relatively high concentrations of 7.5 and 15 g L -1 , equivalent of 25 and 50 mmol L -1 if recalculated to molarity based on quercetin molar mass (302.24 g mol -1 ) (14).…”
Section: Experimental Determination Of Platelet Aggregation and Resulmentioning
confidence: 99%